Anchoring of Consumers' Inflation Expectations: Evidence from Microdata - Lena Dräger; Michael Lamla (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper we explore the degree of anchoring of inflation expectations of consumers by analysing the comovement in short- and long-run expectations. If inflation expectations are firmly anchored, a transitory shock should influence the short-run inflation expectations but not effect long-run inflation expectations. Utilizing the University of Michigan Survey of Consumer s rotating panel microstructure, we can identify and analyse to which extend individuals adjust their short- and long-run inflation expectations within six months. Our results indicate that inflation expectations became more anchored over time. Interestingly, the comovement fell substantially after 1996 which is characterised by the pre-preemptive tightening of the FED and not with the Volker Disinflation. Analysing the probability of revising long- and short-run expectations simultaneously, we find no such structural change in time. Hence, while the comovement has become smaller over time the probability of adjusting long- and short-run expectations has remained unaffected. Looking at the current economic crises the comovement dropped between 2008-09 and since then is rising again. Regarding the possible determinants of the strength of comovement we find that high inflation, higher levels of expected inflation of professional forecasters and news on inflation as well as news on fiscal deficts lead to a greater comovement and hence a lower anchoring of inflation expectations. On the other hand tighter monetary policy improves the degree of anchoring.
Keywords: E31; E58; D84; 330